Implementation of E-Government in the Public Service Process in Karo Regency - Br Majuntak, Wintaria; Hutahaean, Marlan; Riris Pasaribu, Vera Asihna (Iapa Proceedings Conference, 2025)
Importance of administrative completeness in every requirement in registration to obtain services such as school registration, employment status, obtaining health services, obtaining permits, and other services. All require appropriate population administration. However, every human being’s status will change over time, such as employment, marriage, and education. Then it is necessary to make changes. Services for administrative management can already be done online. However, due to a lack of knowledge of technology and information, the implementation of online services is less attractive to the public. This paper aims to examine the digital governance process through the implementation of e-government in the public service process at the Department of Population and Civil Registration, Tanah Karo Regency. The research focus is on implementation performance and the factors that influence the performance of e-government policy implementation. So that researchers can provide research findings that will be used as a reference for the next researcher when comparing implementation performance and factors that influence the current study to the next. Using a qualitative description approach that provides detailed explanations of the problems investigated, it was discovered that the performance of the implementation of population administration services via e-government was as follows: (1) Access to information requirements is easily obtained by the community, but access to all types of services cannot be managed online; (2) People still use online services a little; (3) People still rarely use online services; (4) The implementation of online services is right on target; (5) The process of completing administrative documents is on time; (6) Documents can be printed by the community themselves because their authenticity is guaranteed; (7) Management of documents becomes efficient and effective; Meanwhile, the factors that affect the performance of the first e-government policy implementation are the environmental conditions of the relationship between human resource organizations and the character of the institution. Based on these findings, the proposed policy recommendations need to increase the socialization of services through e-government to the community, carried out by the Information Service Section of the Population and Civil Registration Service of Karo Regency, by inviting the cooperation of sub-district and village officials in providing online service socialization and using social media. Providing service space in each sub- district and village office using the village fund budget, such as the availability of one unit computer, one unit printer, and A4 paper weighing 80 grams, and one person who is able to operate and can teach the community so that the next document management can be done online and can print the results in the office that is already available in the administrative management service room because in the printing place there is not necessarily a paper size like the set.